Evidence that Seat Belts Are as Effective as Child Safety Seats in Preventing Death for Children Aged Two and Up - Levitt, Steven D. (The Review of Economics and Statistics, 2008)
Over the past thirty years, the use of child safety seats in motor vehicles has increased dramatically. There is, however, relatively little empirical evidence regarding the efficacy of child safety seats relative to the much cheaper alternative of traditional seat belts. Using data on all fatal crashes in the United States from 1975 to 2003, I find that child safety seats, in actual practice, do not provide any discernible improvement over adult lap and shoulder belts in reducing fatalities among children aged two to six. Lap-only belts are somewhat less effective, but still far superior to riding unrestrained.